First Order Derivative Spectrophotometric Method for Simultaneous Estimation of Lamivudine, Nevirapine and Zidovudine in Tablets - NAGULWAR, VAISHALI; BHUSARI, KISHOR (Asian Journal of Chemistry, 2010)
A simple, accurate, precise, economical and reproducible first order derivative UV spectrophotometric method is being developed for the simultaneous estimation of lamivudine, nevirapine and zidovudine in pure bulk drug and in tablet dosage form. The stock solutions were prepared in 0.5 M HCl followed by the further required dilutions with distilled water. The peak amplitude for lamivudine, nevirapine and zidovudine were observed at 266.70, 320.31 and 280.38 nm, respectively and linearity was also shown at these wavelengths in concentration range of 5-25, 10-50 and 10-40 μg/mL by all the 3 drugs. The proposed method has estimated lamivudine 98.5 %, nevirapine 99.89 % and zidovudine 99.72 % in marketed tablets. The results of analysis have been validated statistically and also by recovery studies.